Determination of the mixing height for air pollution modeling in tropical regions - Duong Van Minh; Nguyen, Thi Kim Oanh; Luketina, D.A.; Satoh, Hiroyasu; Mark, Ole; Danish International Development Assistance (DANIDA) (Bangkok : Asian Institute of Technology, 2002)
This study has been carried out to determine the mixing height in tropical meteorology condition using graphical and computational methods. Hourly surface and daily upper air observations in 2001 are used at MaeMoh site, Rayong province and at Maptaput site, Lampang province, Thailand. Simple modifications are applied for zero-order mixed layer model of Sven-Erik Gryning and Ekaterina Batchvarova with adaptation of virtual temperature and kinematics virtual potential temperature flux to the existing set of equations. Modifications thus accounted for the effects of moisture content on air density. Consequently the mixing height increased by 3 .2% at MaeMoh site and 1.5% at Maptaput site. Daily minimum and maximum mixing heights are derived from tephigram by Holzworth's graphical method for two cases with and without condensation energy consideration. In this method, affect of the condensation energy on mixing height was also taken into account. Obtained results showed a significant increasing in maximum mixing heights (23.75%). Comparisons to actual measurements obtained from remote sounding systems at both sites present a good agreements with computational results for most of the days in the period of January and December 2001. There are discrepancies shown for the first and the last hour of simulations which may be related to the application conditions of the model.
Thesis (M.Sc.) - Asian Institute of Technology, 2002
A thesis submitted in partial fulfillment of the requirements or the Degree of Master of Science. School of Environment, Resources and Development
Keywords: Tropical meteorology; Air -- Pollution